People participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows a large group of men, women and children participating in the 1986 y-Walk. They are walking in a crosswalk and the woman in the lead is carrying a camera. Some of the participants are wearing tee shirts that read: "Walk for women. YWCA 1986" and some of them are carrying balloons. There is a wooden covered sidewalk directly behind them with a sign that reads: "Pedestria[n] Walkwa[y]." Other signs are posted on the walkway advertising leasing opportunities and builders.